Drug-Coated Balloon for the Treatment of Nonacute Symptomatic Intracranial Carotid Artery Terminus Occlusion: Initial Experience and Follow-Up Outcome - Yin, Hao; Zhang, Jinping; Zhao, Wei; Zheng, Meimei; Song, Yun; Sun, Lili; Zhang, Jun; Han, Ju (Frontiers in Neurology, 2022)
Abstract Background Studies on the recanalization for occlusion of the internal carotid artery terminus are scattered. Recently, drug-coated balloon (DCB) has been increasingly applied in the intracranial artery occlusion and achieved encouraging results. However, there seems no convincing data for the non-acute symptomatic internal carotid artery terminus occlusion (sICATO). Objective To assess the feasibility and effectiveness (safty) of DCB for patients with non-acute sICATO refractory to medical therapy. Approach This study included 30 patients with non-acute sICATO treated with DCBs and/or remedial stenting. The rate of successful recanalization, periprocedural complications and clinical and vascular imaging follow-up outcomes were retrospectively analyzed. Results DCB dilatation of non-acute sICATO gives a 100% rate of successful recanalization, with low complication rate (10.00%), good clinical outcomes (86.20%), low restenosis/reocclusion rate (3.45%) and one asymptomatic ipsilateral infarction (3.45%). Conclusions DCB dilation seems to be the promising treatment option for non-acute sICATO considering its safety and feasibility.